Africa - no more than skin deep in the leather industry - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Animal hides, hair and fur are among the most lucrative primary by-products of the livestock industry. In Africa thevalue-added potential of these by-products is still under-exploited when compared with the importance of livestock. With a few...